Enhancing Health, Access, and Partnerships: National Oral Health Conference - Kim McFarland, DDS, MPH (Blackwell Synergy, 2001)
The 64th annual meeting of the American Association of Public Health Dentistry (AAPHD) was held jointly for the second time with the Association of State and Territorial Dental Directors (ASTDD).